1992
DOI: 10.1159/000186733
|View full text |Cite
|
Sign up to set email alerts
|

Painless Myocardial Ischemia in Chronic Hemodialysed Patients: A Real Event?

Abstract: We investigated the incidence of painless (silent) myocardial ischemia, manifested as S-T segment deviation, by Holier ECG monitoring in patients with chronic renal failure undergoing regular hemodialysis. Forty-five patients underwent Holier ECG monitoring for a continuous 48-hour period covering dialysis and the intermediate period of everyday activity at home. ECG criteria for ischemia were found in 15.5% of patients mainly during and immediately after dialysis with a simultaneous increase of R, S, R+ S amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The echocardiographic findings of dialysisinduced LV RWMA that were seen in both our previous study and in these results are strongly suggestive of subclinical ischemia, analogous to dobutamine stress echocardiography (16). In addition to the work from our center, one study demonstrated dialysis-induced perfusion defects using single photon emission computed tomography (7), and there are 10 reports of silent intradialytic ST depression detected by Holter monitoring (6,(17)(18)(19)(20)(21)(22)(23)(24)(25). Although initially there was concern that some electrocardiographic changes that were observed during dialysis were related to changes in electrolyte concentrations as opposed to myocardial hypoperfusion, the demonstration of dialysis-induced ischemia by electrocardiographic, echocardiographic, and isotopic techniques certainly suggests that such findings are attributable to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The echocardiographic findings of dialysisinduced LV RWMA that were seen in both our previous study and in these results are strongly suggestive of subclinical ischemia, analogous to dobutamine stress echocardiography (16). In addition to the work from our center, one study demonstrated dialysis-induced perfusion defects using single photon emission computed tomography (7), and there are 10 reports of silent intradialytic ST depression detected by Holter monitoring (6,(17)(18)(19)(20)(21)(22)(23)(24)(25). Although initially there was concern that some electrocardiographic changes that were observed during dialysis were related to changes in electrolyte concentrations as opposed to myocardial hypoperfusion, the demonstration of dialysis-induced ischemia by electrocardiographic, echocardiographic, and isotopic techniques certainly suggests that such findings are attributable to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary angiography was not done in most studies; where it was performed, the results did not correlate with SMI during HD. [9,10] Only 20% of the patients developing SMI in this study showed significant epicardial CAD. Angiography delineates coronary anatomy but provides no pathophysiological information about coronary function.…”
Section: Discussionmentioning
confidence: 59%
“…A correlation between LV hypertrophy and SMI has been reported in some studies. [9,10] We used echocardiography, a more sensitive and specific tool compared with surface ECG used in these studies for detecting LV hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have noted the frequent occurrence of transient silent myocardial ischemia during the hemodialysis procedure [7][8][9] . Kremastinos noted silent ischemia among 15% of hemodialysis patients, and he observed that the majority of these episodes were during the latter part of dialysis 10 . Linear regression analysis demonstrated di erences in serum potassium concentration before and after dialysis correlated with the likelihood of demonstrating ischemia.…”
Section: Discussionmentioning
confidence: 99%